Ultrasound machine:possibility and solution for dairy farms in reproduction management - Hatvani, Csilla (Acta Agraria Kaposváriensis, 2010)
There is momentous store from the aspect of reproduction biology in the currently working, dairy farms in Hungary. The solving problems are reduction of the calving interval and the insemination index as well as increasing the number of the cows with their first insemination. Our goal was to check, how can we use the ultrasound scan in the fertility management of a big dairy, and with the use of it, is it possible to get better fertility numbers. We examined dairy cows by rectal ultrasound with a high definition, crossing frequency, and with linear examination head in two Hungarian dairy farms in determine post partum and post insemination. Our examinations shous that ultrasound systems can use well starting from the involution, chosing the first time of the insemination, pregnancy and sterility examinations. The reproduction index can be improved with their help.
Keywords: ultrasound system; examination of early pregnancy; irregular forms in ovaries